Metacommunity analysis of meiobenthos of deep-sediments from the Gulf of Mexico - Cisterna-Céliz,José Alejandro; Marcelino-Barros,Mirayana; Rocha-Olivares,Axayacatl (PeerJ Preprints, 2018)
Background Metacommunity theory is a conceptual framework addressing the interdependence of local interactions and regional processes, especially when communities have no clear boundaries and it is difficult to relate community structure and the environment at different spatial scales. Methods To test the applicability of this theory to meiobenthos, twenty-seven deep-sea sediment samples from the Gulf of Mexico were analyzed for meiobenthic and nematode community distribution and structure along with a set of environmental variables. Results Spatial and temporal heterogeneity in environmental conditions were found among sampling stations; and some variables, such as depth, inorganic carbon, carbon/nitrogen ratio, oxygen and percentage of sand, proved influential on total community abundance. Nematodes were the dominant meiofaunal group and its abundance highly variable among sites and sampling periods. Nematofauna was dominated by bacterivory, which also possessed the highest maturity index. Environmental characteristics showed a significant relation with community structure, not so the dispersal of nematode genera. Discussion In light of our findings we posit that the deep-sea meiobenthos of the Gulf of Mexico may represent a metacommunity following the “species sorting model”. This inference is based on the different taxonomic structures among sampling stations correlating with environmental differences, in the presence of local niche diversification and limited dispersal.
Keywords: Metacommunity; Meiobenthos; Gulf of Mexico; Nematodes; Deep-sea